Digital Library of the Caribbean : crossing borders : TICFIA : Oct. 2005 - Sept. 2009 (Florida International Univ. MiamiUS, 2004)
Presents the application for grants under the Technical Innovation and Cooperation for Foreign Information Access (TICFIA) for New Awards CFDA #84.337A.
Keywords: LIBRARIES